Bổ sung dầu và nitơ phi protein vào khẩu phần để giảm phát thải khí mêtan của bò sinh trưởng - Hiep, Tran; Hoa, Dang; Dang, Pham; Bang, Nguyen; Trach, Nguyen (Tạp chí Khoa học Nông nghiệp Việt Nam, 2024)
A two factorial experiment was carried out in three months (June to August, 2012) at the experimental station of Viet Nam National University of Agriculture to determine the effect of dietary supplementation with four different levels of sunflower oil (SFO) and two different kinds of non-protein nitrogen (NPN) on enteric methane emissions and performance of growing cattle. Twenty-four growing Lai Sind cattle (170 kg on average) were randomly divided into 8 blocks corresponding to 8 diets. Each diet includes 2% NaOH-treated rice straws and cassava leaf meal (1% BW - body weight, dry matter basis) as a basal diet supplemented with one of four SFO levels (1.5%, 3.0%, 4.5%, 6.0%) in combination with 4% calcium nitrate or 1.5% urea as NPN source supplement. Methane emissions was determined by using CH4 to CO2 ratio method. Results showed that methane emissions intensity (l/kg DMI - dry matter intake) was reduced by 26% when using nitrate supplement instead of urea supplement. The increase in oil level in the diet nonlinearly reduced methane emissions. The best level of SFO supplement was 3.0%. However, the best dietary treatment was supplementation with 4% calcium nitrate and 1.5% SF oil. It was also shown that the estimated energy losses as CH4 emissions from the experiment diet ranged from 5-8% gross energy intake, compared with around 12% potential energy loss from diet without supplement. In conclusion, it is suggested that the diets of growing cattle should be supplemented with 4% calcium nitrate and 1.5% oil to mitigate methane emissions.